Christmas card murder [large type] - Meier, Leslie; Hollis, Lee; Ehrhart, Peggy (Thorndike Press large print mystery, 2020)
A collection of three holiday-themed novellas includes Leslie Meier's "Christmas Card Murder," in which the discovery of an old Christmas card with a nasty message finds Lucy Stone investigating a decades-old murder.